Systems change in UK HEIs: how do culture, management, users and systems align?. Issue 6 (17th April 2020) - Skoumpopoulou, Dimitra; Robson, Andrew
Abstract : Purpose: The purpose of the study is to assess the implementation of integrated information systems in UK higher education institutions (HEIs) via multiple internal stakeholders. Design/methodology/approach: The approach analyses the implementation strategy of two HEIs and assesses the impact of new systems on working practices. This involves interviews with various stakeholder groups from the HEIs, capturing 35 interviews. Findings: Results indicate that growth of alternative power bases emerge within both HEIs, as well as new roles and responsibilities for administrative staff, and different working practices for academics. Varying levels of importance are given to people and culture, management support, user involvement and clarity of communication and systems' requirements at project pre-implementation, implementation and post-implementation stages. Practical implications: This study provides lessons of HEIs planning to undertake significant change by implementing integrated information systems. Challenges emerge around fit, complexity, training, communication and consultation. Benefits gained and emerging challenges show some commonality between the two case HEIs, pointing the way forward for other " large " (student number determined) HEIs embarking on similar change. Originality/value: The UK HEI sector is experiencing major change emphasising cost reduction and operational efficiency. Understanding challenges relating to significant systems change in complex settings with varying stakeholder demands has considerable sectoral value.